Pengaruh Lokasi Dan Gaya Hidup Terhadap Keputusan Pembelian Konsumen Di Restoran Jiwa Raga Kitchenette Padang - Resy Putri Utami; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The culinary business is currently one of the most promising business opportunities. However, behind the success of the business there are certainly factors that influence consumers, such as strategic location and lifestyle that is appropriate at this time. This study aims to describe and analyze the influence or impact obtained from location and lifestyle on purchasing decisions at Jiwa Raga Kitchenette Padang Restaurant. This type of research is quantitative with an associative method in the form of a causal relationship. The study population consisted of consumers who visited Jiwa Raga Kitchenette Restaurant with a research sample of 160 samples and the sample was collected by applying purposive sampling technique. The data collection technique used was the distribution of questionnaires to consumers of Jiwa Raga Kitchenette Restaurant. The questionnaire was prepared using a Likert scale and had been tested for validity with the help of SPSS 23.00. The research data were analyzed using multiple linear regression analysis methods, using prerequisite analysis tests, namely normality test, multicollinearity test and heteroscedasticity test. In testing this hypothesis, partial statistical test (t test) and simultaneous statistical test (F test) were used with significance level α = 0.05 (5%). The results of the research data analysis indicate that the independent variables, namely location (X1) and lifestyle (X2), have a positive and significant influence on the dependent variable, namely the purchase decision (Y). The results of the hypothesis test indicate that the location variable has a significantly positive impact on purchasing decisions, as well as the lifestyle variable on purchasing decisions. Overall, the simultaneous test results indicate that both variables, location (X1) and lifestyle (X2), have a positive and significant effect on the purchasing decision variable (Y).